Potential of Pulse Flours as Partial Meat Replacers in Heat-Treated Emulsion-Type Meat Sausages - Mateo, Javier; Caro, Irma; Kasiayan, Seyedalireza; Salvá, Bettit K.; Carhuallanqui, Andrea; Ramos, Daphne D. (Frontiers in Animal Science, 2021)
Reformulation approaches in the meat industry are required to promote nutritional improvement, health functionality and reduce environmental impact. A relevant approach among these is to reduce the amount of meat in meat products. Reduced-meat products should maintain or improve the sensory characteristics and nutritive value compared to conventional meat products. Among meat products, heat-treated emulsion-meat sausages are widely consumed and especially suitable for reformulation approaches. Due to its high protein content, with high functionally and biological value, pulse flour has a high potential to be used as meat replacer. Most studies have been made on fresh meat preparations where amounts of up to 15 % of pulse flour did not negatively affect sensory quality while increased yield and firmness. However, studies using pulse flour in emulsion-type sausages are scarce. Further research is warranted to optimise the reformulation of these meat products using flour pulses. The topics to be addressed are the following: effects of pulse type, pulse pretreatments, such as soaking or germination, pulse flour treatments before incorporation into the meat mix, combination of pulses with other proper ingredients, and heat treatment intensity, on the pulse antinutrient inactivation and the technological and edible quality traits of the pulse-containing sausages.